2022
DOI: 10.3390/nursrep12030042
|View full text |Cite
|
Sign up to set email alerts
|

Australian First-Year Nursing Student Knowledge and Attitudes on Pressure Injury Prevention: A Three-Year Educational Intervention Survey Study

Abstract: Pressure injury prevention is a significant issue as pressure injuries are difficult to heal, painful, and create clinical complications for patients. The aim of this study was to investigate knowledge and attitudes of first-year nursing students to pressure injury prevention, and to explore whether additional educational interventions augmented learning. A previously validated online survey was administered to three cohorts of first-year nursing students in 2016, 2017 (after additional online education), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 25 publications
(52 reference statements)
4
23
1
Order By: Relevance
“…The overall mean knowledge score in this study was 49.9% (11.7 ± 0.1). This is much lower than the scores reported by researchers using the same tool in Australia and other countries, such as Gunningberg et al 24 (58.9%), Simonetti et al 8 (51.1%), Mather et al 29 (55.4%), and Usher et al 15 (51.1%). It is higher than the mean knowledge score found by Kısacık and Sönmez 23 (38.2%) but lower than the 58% reported by Tülek et al 2 in Turkey.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The overall mean knowledge score in this study was 49.9% (11.7 ± 0.1). This is much lower than the scores reported by researchers using the same tool in Australia and other countries, such as Gunningberg et al 24 (58.9%), Simonetti et al 8 (51.1%), Mather et al 29 (55.4%), and Usher et al 15 (51.1%). It is higher than the mean knowledge score found by Kısacık and Sönmez 23 (38.2%) but lower than the 58% reported by Tülek et al 2 in Turkey.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the overall mean PUPKAI score was only 49.9% (11.7/26), and no student could answer all questions correctly; in addition, the overall mean ATPUPI score was 42.20 ± 2.40. A study conducted by Mather et al 29 with 472 student nurses showed that students lacked knowledge despite their positive attitudes toward PIs (mean score, 55.4%). Another study involving student nurses from seven universities in Australia reported a mean knowledge score of 51.1% and an attitude score of 40.8 ± 3.9 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such practice requires strong clinical judgement and appropriate visual assessment. 14 Despite the publication of clinical practice guidelines for the prevention of PUs two decades ago, 15 the incidence rate of these injuries is still high, with 2.5 million people suffering from them annually only in the United States. 16 The prevalence of PUs in various countries and medical settings has a wide range from 0% to 72.5%.…”
Section: Introductionmentioning
confidence: 99%